2011
DOI: 10.1002/cmdc.201100408
|View full text |Cite
|
Sign up to set email alerts
|

Development of Improved PPARβ/δ Inhibitors

Abstract: GSK0660 (1) is the first peroxisome proliferator-activated receptor (PPAR) β/δ-selective inhibitory ligand described in the literature. Based on its structure, we designed and synthesized a series of modified compounds to establish preliminary structure-activity relationships. Most beneficial for increased binding affinity towards the PPARβ/δ ligand binding domain was the replacement of the 4'-aminophenyl substituent by medium-length n-alkyl chains, such as n-butyl or iso-pentyl. These compounds show activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…Pharmacokinetic studies have shown that the bioavailability of ST247 is as poor as that of the parent compound (study performed at Cerep, Redmond, WA; data not shown). However, the analysis of further derivatives has provided preliminary evidence that certain positions in the molecule can be modified without a loss of affinity or specificity (Toth et al, 2011). The linkage of suitable side groups to these positions is a potential strategy to improve the bioavailability of ST247 and is currently pursued in our laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies have shown that the bioavailability of ST247 is as poor as that of the parent compound (study performed at Cerep, Redmond, WA; data not shown). However, the analysis of further derivatives has provided preliminary evidence that certain positions in the molecule can be modified without a loss of affinity or specificity (Toth et al, 2011). The linkage of suitable side groups to these positions is a potential strategy to improve the bioavailability of ST247 and is currently pursued in our laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…DG172, its derivatives, and ST247 were synthesized as previously described (Lieber et al, 2012;Toth et al, 2012). GW501516 was purchased from Axxora (Lörrach, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Synthetic antagonistic ligands for PPARb/d have been explored to a much lesser extent, but several inhibitory compounds have been described over the past years. These include the irreversible inhibitor and partial PPARg agonist GSK3787 (Palkar et al, 2010;Shearer et al, 2010), the PPARb/dspecific GSK0660 (Shearer et al, 2008) and its improved derivative methyl 3-{N-[4-(hexylamino)-2-methoxyphenyl]sulfamoyl} thiophene-2-carboxylate (ST247) (Naruhn et al, 2011;Toth et al, 2012), and the stilbene (Z)-2-(2-bromophenyl)-3-{[4-(1-methylpiperazine)amino]phenyl}acrylonitrile (DG172) (Lieber et al, 2012). These ligands act as inverse agonists, as indicated by their inhibitory effect on the basal expression of PPARb/d target genes and an increased recruitment of transcriptional corepressors (Naruhn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Toward this goal, we made use of recently developed subtype-specific PPARβ/δ inhibitors (ST247, DG172; Figure 1a), which downregulate expression of ANGPTL4 by acting as inverse agonists through an unknown mechanism. 30, 31, 32 Inverse agonists are defined as ligands that, beyond antagonizing agonist binding, exert an opposite effect as an agonist. Thus, in case of PPARβ/δ, an agonist induces a transcriptional activator complex by facilitating the association of PPARβ/δ with coactivators, whereas an inverse agonist triggers the recruitment of transcriptional corepressors and thereby the formation of a repressor complex.…”
Section: Introductionmentioning
confidence: 99%